Step-by-step explanation:
start from f(g(x))
f(g(x))= 3(g(x)) -2
f(g(x))= 6x -2
h(f(g(x)))=(f(g(x)))² -5(f(g(x)))
h(f(g(x)))=(6x-2)² -5(6x-2)
h(f(g(x)))=36x²-24x+4-(30x-10)
h(f(g(x)))=36x²-24x+4-30x+10
h(f(g(x)))=36x²-54x+14
Answer:
24°
Step-by-step explanation:
the total angle, made up from both a and 66°, is a mini-square, as you can see. this represents a right angle of 90°
thus, a and 66° combine to make 90°
a + 66° = 90°
subtract 66 from both sides to get a
a = 24°
3 , 4 and 6 are not correct
Answer:
->a is 2
->b is one eight
Step-by-step explanation:
one fourth dividen in two becomes one eight.